Development procedural theory of financial law - Kasianenko, Liubov Mykhailivna (Державний податковий університет, 2021)
Procedural financial and legal theory, first of all, is associated with the development of the corresponding categorical apparatus. The theoretical sources regarding the concepts of «the process» and «the procedure» are analyzed in the article, as well as among scientists there is no consensus about these terms. The content of the concept «the legal process» and «the legal procedure» is quite close, almost synonymous, moreover, that this proximity explains common root in the Latin word correspondence. In the static sense, it is established in the legal order or practice, the order of carrying out of certain actions. The activity would even be disorganized and chaotic without this, and it was impossible to organize social relations. In the dynamic sense, a process or procedure can be considered as a practical implementation of the established order by issuing legal acts, making decisions and taking certain actions for their implementation. The establishment of financial and procedural legal theory, first of all, is connected with the development of appropriate categorical apparatus, which is represented as a network of basic notions of scientific thinking and so it ensures its unity, integrity and constant reproduction. In our opinion, a broad understanding of the process should facilitate a deeper scientific study and comprehension of this category. Many researchers attribute the concept of legal process to such legal categories as action, activity and equate it with categories that characterize the form, the formal side of the legal status, actions, etc. As the financial activity of the state government and local self-government bodies generally has procedural order, it requires legal regulation not less than, for example, judicial activity. Taking into account the scholars’ research, it is suggested that the procedural form is inherent in any financial activity, and the widespread opinion that only legal proceedings can be carried out in a special procedural form is insufficiently reasoned. The meaning of any activity is disclosed through a set of consistent actions carried out by its subjects. In our opinion, in order to determine the objective limits of the financial and legal process, it is necessary to proceed from the main directions and functions of financial activity of the state and local self-government bodies which should be expedient, oriented on the implementation of legitimate state and public interests, carried out in the appropriate procedural form, which must conform to the principle of legality, be rational, free of empty formalities.

Процесуальна фінансово-правова теорія насамперед пов’язана з розробкою відповідного категоріального апарату. У статті проаналізовано теоретичні джерела щодо понять «процес» та «процедура», а також серед науковців немає єдиної думки щодо цих термінів. Зміст понять «юридичний процес» і «юридична процедура» досить близький, майже синонімічний, до того ж саме ця близькість пояснює спільнокореневі в латинському слові «кореспонденція». У статичному розумінні це встановлює в правовому порядку чи практиці порядок здійснення певних дій. Без цього діяльність була б навіть неорганізованою і хаотичною, а суспільні відносини організувати неможливо. У динамічному розумінні процес або процедуру можна розглядати як практичну реалізацію встановленого порядку шляхом видання правових актів, ухвалення рішень та здійснення певних дій для їх реалізації. Становлення фінансово-процесуальної правової теорії насамперед пов’язане з розробкою відповідного категоріального апарату, який представлений у вигляді мережі основних понять наукового мислення і так забезпечує його єдність, цілісність і постійне відтворення. На нашу думку, широке розуміння процесу має сприяти більш глибокому науковому вивченню та осмисленню цієї категорії. Багато дослідників відносять поняття юридичного процесу до таких правових категорій, як дія, діяльність, і ототожнюють його з категоріями, що характеризують форму, формальний бік правового статусу, дії тощо. Оскільки фінансова діяльність органів державної влади та місцевого самоврядування загалом має процесуальний порядок, вона потребує правового регулювання не менше ніж, наприклад, судова діяльність. Враховуючи дослідження вчених, висловлюється припущення, що будь-якій фінансовій діяльності притаманна процесуальна форма, недостатньо обґрунтованою є поширена думка про те, що тільки судочинство може здійснюватися в спеціальній процесуальній формі. Сенс будь-якої діяльності розкривається через сукупність послідовних дій, що здійснюються її суб’єктами. На нашу думку, для визначення об’єктивних меж фінансово-правового процесу необхідно виходити з основних напрямів і функцій фінансової діяльності держави та органів місцевого самоврядування, які мають бути доцільними, орієнтованими на реалізацію законних державних і громадських інтересів, здійснених у відповідній процесуальній формі, яка повинна відповідати принципу законності, бути раціональною, вільною від порожніх формальностей.
Keywords: financial and legal process; financial responsibility; process; procedure; procedural theory of financial law; фінансово-правовий процес; фінансова відповідальність; процес; процедура; процесуальна теорія фінансового права